(untitled) (Groundings Undergraduate, 2013)
Giacomo Puccini (1858-1924), the famous Italian composer, has been described as a cynic towards the Catholic Church, despite having been brought up in arguably one of the most Catholic countries of Europe. The Church was equally mistrusting of him, especially after the first performances of Tosca, one of his most famous works. In this opera his antipathy towards the Catholic Church as an institution is expressed clearly through the narrative, where the struggle of the individual against the corrupted power of the Church is represented as a personal struggle between two individuals who represent the opposite sides of this conflict. However, a more interesting aspect is how Puccini has employed musical techniques to dramatise the power struggle and reflect the shifting of power from one character to the other.